CLINICO-RADIOLOGICAL FINDINGS IN PEDAL MYCETOMA—A CASE REPORT - MUNIVENKATAPPA, KRISHNA KUMAR; Lokesh. C; Senthilnathan. V (International Journal of Radiology and Imaging, 2024)
One of the common granulomatous disorders affecting the skin and subcutaneous soft tissues, Madura mycosis or mycetoma is typically observed in tropical areas. Early diagnosis of mycetoma, which may be treated, depends on radiological imaging. Recently, the "dot-in-circle" sign on magnetic resonance imaging (MRI) and ultrasound has been described in patients with Madura mycosis. After a year of elaboration, a 55-year-old man with easily swollen and leaking sinuses on the dorsal aspect of the left distal foot was diagnosed with mycetoma. The objective of this case study is to link radiological and clinical results in a mycetoma case. Functional and morphological damage can be limited with an early and accurate diagnosis based on imaging results, histological analyses, and microbiological assessments. Keywords: pedal mycetoma, Madura mycosis, dot-in-circle sign, and chronic granulomatous illness.